Causal associations of ischemic stroke, metabolic factors, and related medications with epilepsy: a Mendelian randomization study - Wang, Wencai; Liu, Menghao; Liu, Fengling; Wang, Zun; Ye, Wei; Li, Xianfeng (Frontiers in Neurology, 2024)
BackgroundEarlier researches have demonstrated that ischemic stroke, metabolic factors, and associated medications may influence the risk of epilepsy. Nevertheless, the causality between these elements and epilepsy remains inconclusive. This study aims to examine whether ischemic stroke, metabolic factors, and related medications affect the overall risk of epilepsy.MethodsWe used single nucleotide polymorphisms associated with ischemic stroke, hypothyroidism, hypertension, blood glucose levels, high cholesterol, serum 25-Hydroxyvitamin D levels, testosterone, HMG CoA reductase inhibitors, and beta-blocking agents as instrumental variables in a Mendelian randomization technique to investigate causality with epilepsy. Multiple sensitivity methods were performed to evaluate pleiotropy and heterogeneity.ResultsThe IVW analysis revealed positive associations between ischemic stroke (OR = 1.29; p = 0.020), hypothyroidism (OR = 1.05; p = 0.048), high blood pressure (OR = 1.10; p = 0.028), high cholesterol (OR = 1.10; p = 0.024), HMG CoA reductase inhibitors (OR = 1.19; p = 0.003), beta-blocking agents (OR = 1.20; p = 0.006), and the risk of epilepsy. Conversely, blood glucose levels (OR = 0.79; p = 0.009), serum 25-Hydroxyvitamin D levels (OR = 0.75; p = 0.020), and testosterone (OR = 0.62; p = 0.019) exhibited negative associations with the risk of epilepsy. Sensitivity analyses confirmed the robustness of these findings (p > 0.05).ConclusionOur research suggests that ischemic stroke, hypothyroidism, high blood pressure, high cholesterol, HMG CoA reductase inhibitors, and beta-blockers may increase the risk of epilepsy, whereas serum 25-Hydroxyvitamin D levels and blood glucose levels may reduce the risk.